2007
DOI: 10.1088/0954-3899/34/7/017
|View full text |Cite
|
Sign up to set email alerts
|

S-wave andP-wave ππ andKπ contributions to three-body decay processes in the Resonance- Spectrum Expansion

Abstract: We study S-and P -wave ππ and Kπ distributions for the three-body production pro-, by applying the Resonance-Spectrum Expansion to the two-body subamplitudes. The results are compared to the corresponding signals reported by the BES, E791 and FOCUS collaborations. We find that the studied S-and P -wave channels can largely account for the observed structures in the data up to 1 GeV.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 46 publications
(164 reference statements)
1
14
0
Order By: Relevance
“…In a very recent article [1] we have shown that several hadronic three-body decays of J=w; D and D s mesons can be well described, up to moderately high energies, in a model for production processes derived from the so-called Resonance-Spectrum Expansion (RSE) [2]. The RSE formalism amounts to an effective description of non-exotic meson-meson scattering, based upon quark-antiquark pair creation and annihilation allowing transitions between an infinity of confined q q states and the meson-meson continuum.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a very recent article [1] we have shown that several hadronic three-body decays of J=w; D and D s mesons can be well described, up to moderately high energies, in a model for production processes derived from the so-called Resonance-Spectrum Expansion (RSE) [2]. The RSE formalism amounts to an effective description of non-exotic meson-meson scattering, based upon quark-antiquark pair creation and annihilation allowing transitions between an infinity of confined q q states and the meson-meson continuum.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, exact analyticity and unitarity properties, as well as a correct (sub)threshold behaviour, are manifestly satisfied. Moreover, the resulting meson-meson production amplitude can be derived exactly, too, by summing the corresponding two-body Born series, the only assumption being that the third particle acts as a mere spectator [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, in Ref. [2] we showed that such a twoparticle production amplitude can reasonably describe experiment in an energy region where no additional resonances from possible rescattering with the spectator particle exist. Moreover, no need to treat a sizable fraction of the experimental signal as background was noticed.…”
mentioning
confidence: 81%